Standard specifications for transportation materials and methods of sampling and testing and AASHTO provisional standards (American Association of State Highway and Transportation Officials, 2015)
The five-volume Materials Book and Provisional Standards set contains 479 specifications, test methods, and provisional standards -- including 71 revised and 19 new -- commonly used in the construction of highway facilities. 2015. 4,652 pp, 5 volumes.
"Adopted by the American Association of State Highway and Transportation Officials (AASHTO)."
Includes index.
Part 1A: Specifications M 6 - M 288.
Part 1B: Specifications M 289 - R 69.
Part 2A: Tests T 2 - T 237.
Keywords: Road materials -- Standards -- United States.; Road materials -- Testing -- Standards -- United States.; elektronické knihy; electronic books